Determinants of vaccination status among Somali children: evidence from a Countrywide cross-sectional survey - Mohamed Said Hassan; Md. Moyazzem Hossain (BMC Pediatrics)
Abstract Background Immunization is the process of administering a vaccine to stimulate the development of immunity against an infectious agent, with the primary goal of preventing the illness that the infection causes. The authors aim to examine determinants of vaccination coverage among Somali children. Methods The authors used secondary data from the Somali Demographic Health Survey (SDHS)-2020. After removing the missing values, the final sample consists of 9290 children under 5 years of age. The study used descriptive statistics with percentages and frequencies. It also used chi-square to check the association between risk factors and vaccination status. Multivariate logistic regression is employed to analyze the data. Results Findings revealed that the determinants of vaccination were the child’s current age (AOR: 0.624; 95% Cl: 0.489, 0.797), maternal education level (AOR: 0.706; 95% Cl: 0.588, 0.849), family income level (AOR: 0.390; 95% Cl: 0.316, 0.483), number of ANC visit (AOR: 0.369; 95% Cl: 0.293, 0.464), birth order (AOR: 1.303; 95% Cl: 1.098, 1.548) and residence (AOR: 0.643; 95% Cl: 0.548, 0.755). Mothers who have high levels of education have a high chance of vaccinating their children. Conclusion The study identified child age, birth order, maternal level of education, residence, family income, and number of ANC visits, were the contributors to the low vaccination intake among children. Women from poor households, with low educational levels, and who have the least visits to ANC should be targeted to increase the vaccination coverage of Somali children. Therefore, there is a need for policymakers to develop interventions targeting the less focused groups that aim at solving the problem.